Midgut Volvulus Adds a Murine, Neutrophil-Driven Model of Septic Condition to the Experimental Toolbox - Elrod, Julia; Kiwit, Antonia; Lenz, Moritz; Rohde, Holger; Börnigen, Daniela; Alawi, Malik; Mohr, Christoph; Pagerols Raluy, Laia; Trochimiuk, Magdalena; Knopf, Jasmin; Reinshagen, Konrad; Herrmann, Martin; et al. (Cells, 2023)
Background: Severe infections that culminate in sepsis are associated with high morbidity and mortality. Despite continuous efforts in basis science and clinical research, evidence based-therapy is mostly limited to basic causal and supportive measures. Adjuvant therapies often remain without clear evidence. The objective of this study was to evaluate the septic volvulus ischemia-reperfusion model in comparison to two already established models and the role of neutrophil extacellular traps (NETs) in this model. Methods: The technique of the murine model of midgut volvulus was optimized and was compared to two established models of murine sepsis, namely cecal ligation and puncture (CLP) and intra-peritoneal (i.p.) injection of lipopolysaccharide (LPS). Results: Midgut volvulus for 15 min caused a comparable mortality (38%) as CLP (55%) and peritoneal LPS injection (25%) at 48 h. While oxidative stress was comparable, levels of circulating free DNA (cfDNA), and splenic/hepatic and pulmonary translocation of bacteria were decreased and increased, respectively at 48 h. DNases were increased compared to the established models. Proteomic analysis revealed an upregulation of systemic Epo, IL-1b, Prdx5, Parp1, Ccl2 and IL-6 at 48 h in comparison to the healthy controls. Discussion and Conclusion: Midgut volvulus is a stable and physiological model for sepsis. Depending on the duration and subsequent tissue damage, it represents a combination of ischemia-reperfusion injury and hyperinflammation.
CRIS-Team Scopus Importer:2023-02-17
Keywords: CLP; extracellular DNA; LPS; sepsis; sepsis model; volvulus